Distributional Effects of Emission Pricing in a Carbon-Intensive Economy: The Case of Poland - Marek Antosiewicz; J. Rodrigo Fuentes; Piotr Lewandowski; Jan Witajewski-Baltvilks (Institute of Labor Economics (IZA), 2020)
In this paper, we assess the distributional impact of introducing a carbon tax in Poland. We apply a two-step simulation procedure. First, we evaluate the economy-wide effects with a dynamic general equilibrium model. Second, we use a microsimulation model based on household budget survey data to assess the effects on various income groups and on inequality. We introduce a new adjustment channel related to employment changes, which is qualitatively different from price and behavioural effects, and is quantitatively important. We nd that the overall distributional effect of a carbon tax is largely driven by how the revenue is spent: distributing the revenues from a carbon tax as lump-sum transfers to households reduces income inequality, while spending the revenues on a reduction of labour taxation increases inequality. These results could be relevant for other coal-producing countries, such as South Africa, Germany, or Australia.
Keywords: H23; P18; O15; 330; climate policy; carbon tax; distributional effect; microsimulation; general equilibrium; employment